Engaging Students in Social Emotional Learning During the COVID-19 Pandemic: The Lived Experience of Three High School Teachers in the United States - Janna Jobel; Rebecca Lloyd (Canadian Society for Studies in Education, 2023)
Although Social Emotional Learning (SEL) is recommended for grades K-12, research suggests that what is effective in elementary and middle schools-having a separate SEL curriculum-is less effective in high schools (Yeager, 2017). Instead, engaging high school students in SEL through pedagogic practice and the subject area curriculum is encouraged. To do this, high school teachers need SEL instruction and supports, but report few available opportunities (Hamilton et al., 2019). Additionally, few SEL studies exist in the secondary context to help guide high school teachers, and the COVID-19 pandemic further emphasized the need for SEL. To begin to address this gap in SEL research, a series of classroom observations and interviews were conducted to better understand three high school teachers' lived experiences of SEL. Using an approach inspired by Max van Manen's (2016) hermeneutic phenomenology, a common theme emerged. The teachers all identified adapting the pace of curriculum during the COVID-19 pandemic as a phenomenon that inherently engaged students in SEL. The implications of this finding for teacher education and professional learning are considered.